Motor Abilities And Focus Of Attention And Their Relationship To Accuracy Of Scoring From Movement In Football (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the relationship between motor abilities and its relationship to the accuracy of scoring from movement in football, and to identify the relationship between concentration of attention and its relationship to the accuracy of scoring from movement in football. Therefore, the tow researchers intended to use the descriptive method using the correlational method. The current researchers population consists of Al-Sinaa Sports Club football players for the year (2023/2024) participating in the first division league that qualifies for the Iraqi Elite League, where the current researche population consists of (24) players deliberately chosen by the tow researchers, from whom the research chose a sample of (16). ) players after I excluded the goalkeepers (3), and I also excluded (5) players as a result of the knowledgeable reconnaissance experiment, and all of these methods were done in a random manner. After seeking the help of experts, the tow researchers chose the following tests (test of motor abilities, running the plover using the (Barrow) method, 3 The tow researchers used the statistical package SPSS (version 25) to process the results, and the tow researchers concluded that motor abilities and concentration of attention play a major role in the accuracy of scoring from movement in soccer, and that there is a significant correlation between motor abilities and accuracy of scoring from movement in soccer. There is a significant correlation relationship Between focusing attention and scoring skill through football movement.